Application of principles of multimodal analgesia as the content element of a fast-track surgery program - O. Yu. Ioffe; O. P. Stetsenko; M. S. Kryvopustov; T. V. Tarasiuk; Yu. P. Tsiura (Клінічна хірургія)
Objective. To estimate the efficacy of postoperative pain reduction in first days after surgical intervention in acceleration of postoperative restoration in patients and reduction of the stationary treatment duration.